Comparison Of Regulations For The Approval Of Condominium Developments Before And After The Job Creation Law - Qudsi, Mohammad Syafiq; Sukarmi, Sukarmi; Koeswahyono, Imam (IJBLE Scientific Publications Community Inc., 2024)
Housing development is an effort to meet one of the basic human needs, as well as to improve the quality of the living environment, give direction to regional growth, expand employment and drive economic activities in improving and equitable distribution of people's welfare. The construction of flats is one alternative solution to the problem of housing and settlement needs, especially areas in urban areas where the population continues to increase, because the construction of flats can reduce land use, make urban open spaces more spacious and can be used as a way to rejuvenate the city for slums. Arrangements related to the construction of flats were initially regulated in the Flats Law, one of which regulated the ratification of flats. The Job Creation Law through its omnibus law model amends several provisions including those related to flats, including through implementing regulations. In this paper using normative juridical research methods, the author will compare the arrangement for the ratification of flats before and after the promulgation of the Job Creation Law and explore potential juridical problems.